Leuko-glycemic Index as a Prognostic Factor after Acute Myocardial Infarction with ST-segment Elevation - Ailed Rodríguez Jiménez; Raikel Fardales Rodríguez; Enrique Toledo Rodríguez; Guillermo Quintana Cañizarez (Universidad de las Ciencias Médicas de Cienfuegos, 2019)
Foundation: blood glucose and leukocyte count at admission have shown prognostic significance in patients with myocardial infarction. Leuko-glycemic index is a recently proposed marker as a predictor of mortality. Objective: to evaluate the usefulness of the leuko-glycemic index in the stratification of the risk of in-hospital death after STEMI. Method: a prospective observational study was conducted which included all patients admitted consecutively with a diagnosis of acute myocardial infarction with ST segment elevation and Killip> I class, from January 2012 to June 2015 at the Provincial University Hospital Camilo Cienfuegos Gorriarán. Clinical, laboratory and echocardiographic data were collected and the prognostic implication of the leuko-glycemic index in in-hospital mortality was determined through binary logistic regression. The studied variables were: age, sex and color of the skin, medical history and cardiovascular risk factors, clinical data such as systolic and diastolic blood pressure as well as heart rate at admission. Results: LGI was a predictor of mortality in both diabetic and non-diabetic patients (c = 0.673 and c = 0.707) respectively. There was a positive correlation between the Killip class and the leuco-glycemic index (r: 0.471 p <0.001). The 75th percentile showed an acceptable sensitivity and good specificity as a predictor of complications and mortality after STEMI. Conclusions: the leuko-glycemic index in the course of an acute myocardial infarction can be associated with a higher in-hospital mortality. Its detection would be useful in the prognostic stratification of acute coronary syndrome.